2021
DOI: 10.46827/ejfl.v5i5.3890
|View full text |Cite
|
Sign up to set email alerts
|

Factors Influencing Teenager's Motivation in Learning English in Uzbekistan – A Case Study of Westminster International University in Tashkent, Pre-Foundation Course

Abstract: Motivation carries a key role while learning a foreign language. Understanding the motivators and factors which impact students’ motivation would help to improve the quality of the lessons. Thus, this study aims to identify the main motivator in acquiring the English language among teenage students at the Pre-Foundation course of Westminster International University in Tashkent. The research also finds out general impressions of students towards their teachers, parents, and group mates at the course. Quantitat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 9 publications
0
0
0
Order By: Relevance
“…Based on the result obtained by Quiñonez et al (2020)Mamadaminova & Khadjikhanova (2021) concluded that teachers must constantly train for better performance as professionals and implement or change the strategies or activities for listening in class. However,Gilakjani & Sabouri (2016),Saraswaty (2018) & Namaziandost et al, (2019 recommended that teacher should vary their strategies, once they have analyzed the challenges that their students present.…”
mentioning
confidence: 99%
“…Based on the result obtained by Quiñonez et al (2020)Mamadaminova & Khadjikhanova (2021) concluded that teachers must constantly train for better performance as professionals and implement or change the strategies or activities for listening in class. However,Gilakjani & Sabouri (2016),Saraswaty (2018) & Namaziandost et al, (2019 recommended that teacher should vary their strategies, once they have analyzed the challenges that their students present.…”
mentioning
confidence: 99%